Adenosine deaminase behavior in experimental infection by Brucella ovis and its participation in the modulation of the inflammatory response - Perin G.* (2019)
© 2018, Springer-Verlag London Ltd., part of Springer Nature.The objective of this study was to evaluate the activity of adenosine deaminase (ADA) and its participation in the modulation of the inflammatory responses of mice experimentally infected with B. ovis. We used 48 animals, divided in two groups: group A (control) and group B (infected). We evaluated ADA activity and C-reactive protein (CRP) concentrations at four time points (days 7, 15, 30, and 60) post-infection (PI). There was a reduction in ADA activity in the acute phase (day 15 PI), followed by elevation when the infection became chronic (days 30 and 60 PI). Serum C-reactive protein levels were higher in infected animals than in the control group at all time points post-infection (P < 0.05). ADA regulates levels of extracellular adenosine, an anti-inflammatory molecule, suggesting that the enzyme had different behaviors depending on the stage of infection, i.e., ADA had anti-inflammatory action in the acute phase, but with the chronicity of the disease, the ADA had pro-inflammatory action. Therefore, we conclude that ADA participates in the pathogenesis of experimental ovine brucellosis.